Simulation of Resource Monitoring and Discovery in Grids - González Márquez, D. (2010)
The proliferation of huge computer centers with thousands of processors available, summed up with the new computing paradigms as cloud computing, make distributed environment a maze of new perspectives. Dynamics of resource information is increasing in complexity, and nowadays is almost impossible to be captured using a static hierarchy. Consequently, we focused on developing new tools to attack this new challenges. Grid-Matrix is a framework with an user-friendly GUI, based on the famous grid simulator SimGrid. It is focused on the analysis of information propagation policies, including automatic generation of very varied network topologies, and many different policies scenarios. As a case study, we present the generation of clique and ring networks under three different policies: hierarchical, super-peer and random. These preliminary results shows the potential of this powerful framework, plenty of features for the profound analysis of information propagation.